Students’ perceptions of watching English movies with English subtitle in improving vocabulary - Damayanti, Luthfiyah Eka Safa; Nur Ekaningsih; Mandalones, Nichole P.; Nugroho, Kurniawan Yudhi (CV. Yudhistt Fateeh, 2025)
Mastering vocabulary is the fundamental of learning English. However, learning vocabulary is challenging for high school students, especially for those who find traditional learning tools not attractive. English movies with English subtitle are commonly used because it is accessible and contextual. The purpose of this study was to explore grade 10 students’ perceptions of watching English movies with English subtitle for their vocabulary improvement. While many previous studies explored perceptions of this learning strategy in college setting. However, it is needed to explore in high school settings. This research used a mixed-method approach with the questionnaire and interview as the instruments. The respondents were 39 students from grade 10 in a public school in the Philippines. The results showed that students have positive perceptions on English movies with English subtitle for vocabulary improvement, as it helps to enhance vocabulary, understanding of the movies, contextualized and flexible learning tool as well as to improve speaking and listening skills.